Tracing the Continued Existence of Ulayat Land: Granting Management Rights in the Context of Protecting the Rights of Indigenous Peoples - Ma'ruf, Ali; Yakin, Moh. Ainul; Putri, Ervita Septyanto; Karimah, Erlisa Akhlakul; Moechthar, Oemar (Fakultas Hukum Universitas Airlangga, 2024)
AbstractThe issue of granting management rights over ulayat land to third parties is still being debated. Management rights originating from communal land are contrary to the concept of the management right itself. Management rights, which are part of the authority of State control rights, are contradicted by management rights that can originate from ulayat land because indigenous peoples have ulayat rights on the ulayat land. For ulayat land that still has the status of ulayat rights of indigenous peoples, if given management rights, the ulayat rights must be released by the indigenous peoples. Thus, the communal land becomes free state land. The granting of management rights on ulayat land is becoming increasingly relevant and complex. Several changes related regulations have raised significant questions regarding the existence of ulayat land and its impact on the sustainability of the lives of indigenous peoples. To accelerate the economy, the government needs to pay attention to the ulayat rights of indigenous peoples over their ulayat land and ensure that these rights are protected and respected. The government also needs to ensure that effective national law enforcement mechanisms are in place to resolve ulayat land disputes. As a result of the granting of HPL on ulayat land, legal uncertainty arises. The existence of ulayat land for indigenous peoples is very important in maintaining the identity, culture, and sustainability of indigenous peoples. Ulayat rights protect the rights of ownership and management of communal land by indigenous peoples so that they can continue cultural practices, traditions, and customs that have existed since the time of their ancestors.Keywords: Management Rights; Ulayat Land; Indigenous People.